Love as Merit, Grief as Practice: Buddhist Narrative Ethics in the Memoir Mengenang Mama Linda - Latifah Latifah (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Abstract This study examines how the text reframes personal grief as a Buddhist ethical practice, articulating love as karmic merit (puñña) and mourning as a ritualized form of spiritual cultivation (bhāvanā). This study employs narrative ethics and close reading to analyze Hendry Filcozwei Jan’s memoir Mengenang Mama Linda: Wanita Luar Biasa nan Penyayang (2023). The analysis demonstrates that the memoir integrates Theravāda doctrine, Confucian filial piety, and Indonesian cultural rituals to construct a hybrid narrative of healing. The findings reveal that Jan’s literary practice functions as dāna (generosity), transforming private loss into a communal moral resource. This research contributes to Buddhist literary studies by providing a granular model of how contemporary Southeast Asian memoirs navigate grief through narrative ethics, offering an alternative to Western paradigms focused on individual catharsis.